Explaining the Effect of Tribal Structures on Political Decision-Making: A Case Study of Post-2001 Afghanistan - Sayed Israr Samim; Ridwan Ridwan; Aizizuddin Nijat; Mubarak Sha Hassan (Andalas Institute of International Studies UNAND, 2026)
This study examines how tribal structures as informal institutions affect the political decision-making process in Afghanistan between 2001 and 2021. Tribal structures refer to social relations based on tribes, which bring together groups of people and help them influence social life. These structures are often referred to as Khan, Malik, Mashran, Jirga, and Shora in Afghan society. This study employs the informal institution theory as its theoretical framework. Primary data was collected through semi-structured interviews with two categories of participants (tribal structures and politicians). The study relies on secondary data sources such as books, journal articles, reports, policy documents, and websites for its theoretical foundations. The study finds that tribal structures have a considerable impact on shaping local and regional political decision-making through local kinship systems and community councils. In contrast, their influence on national-level political decision-making is limited due to a centralised institutional system, a clear decision-making process according to the constitution and external pressure. By examining Afghanistan's tribal structures, the article contributes to the broader international relations discourses on state-building, state legitimacy, and informal governance in weak and post-conflict states. Additionally, the findings are expected to raise awareness among politicians regarding the informal influence of tribal structures and their impact on political decision-making, thus contributing to both scholarly discourse and practical governance.